Knowledge and practice about prevention on Hepatitis-B virus infection among the student nurses (Asian Journal of Medical and Biological Research, 2021)
The silent killer Hepatitis-B is a major threat to public health throughout the world and well recognized occupational risk for healthcare workers. Good knowledge and practice about hepatitis- B virus (HBV) infection prevention is crucial for HBV infection control. In Bangladesh, there were few studies conducted regarding the knowledge and practice level of student nurses’ about HBV infection prevention. The purpose of this study was to assess the knowledge and practice level of student nurses’ about HBV infection prevention in Bangladesh. A cross-sectional descriptive type of study was conducted in three nursing colleges at Sylhet in Bangladesh. A pre-tested self-administered structured questionnaire with observation checklist was constructed and implemented to assess knowledge and practice about HBV infection prevention. A total of 150 student nurses’ from three nursing college were participated in this study. Data were analyzed using descriptive statistics and Chi-square test was used implemented to determine the relationship between categorical variables. The result shows that most of the respondents (83.3%) were female and mean age was 20±8.72 years. The level of knowledge was good (81.07%) and practice level was satisfactory (72.22%) on HBV infection prevention related activities. Most of the respondents had accurate concepts about HBV infection can be prevented by 96% vaccination, 83.33% safe sex, 92.63% use of disposable syringe, 84.67% wearing gloves during patient care and 78% promote public awareness. The study findings concluded that the majority of the respondents had good knowledge and satisfactory practice level in HBV infection prevention. However, not all of them with good knowledge carried out good practices about to HBV infection prevention in their working place. Authority should be ensuring vaccination status and periodical training program to maintain continued good level of knowledge and practice for prevention HBV infection.Asian J. Med. Biol. Res. 2021, 7 (4), 312-322